Expression of neuritin in human lung squamous cell carcinoma - Liang, Mengjie; Song, Yin; Zhang, Wen; Xu, Feng; Ba, Pengfei; Yang, Li; Huang, Jin (Translational Cancer Research, 2019)
Background: This study aimed to investigate the expression of neuritin in four common cancers, and to explore the association between neuritin expression and the occurrence and development of cancer. Methods: We initially examined neuritin expression in human cervical, endometrial, oesophageal, and lung cancer tissues by immunohistochemistry (IHC). Based on these results, we further examined its expression in lung squamous cell carcinoma (LUSC) tissues by IHC and reverse transcription-polymerase chain reaction (RT-PCR). Results: Neuritin expression levels were higher in all cancer tissues compared with normal control tissues. Neuritin protein and gene expression levels were significantly higher in LUSC tissues compared with normal lung tissues (P